(untitled) (Prithvi Academic Journal, 2025)
This study examines the implications of monetary policy on Nepal’s balance of payments (BOP) using advanced time series techniques, including the Augmented Dickey-Fuller test, Johansen cointegration, Vector Error Correction Model (VECM), and Impulse Response Function (IRF) using data from 1975-2023 . The analysis explores the long- and short-run dynamics of monetary policy instruments—exchange rates, interest rates, money supply, and remittances—while accounting for structural breaks due to economic transitions, political instability, and external shocks. Key findings indicate a significant long-term equilibrium relationship among the variables, with exchange rate depreciation and higher interest rates adversely affecting the BOP, while money supply expansion exerts a positive influence. Notably, remittance inflows exhibit a counterintuitive negative relationship, suggesting inefficiencies in their utilization. The VECM results highlight a robust short-term adjustment mechanism, underscoring the role of exchange rate management and monetary policy in maintaining external stability. This research provides valuable insights into the interplay between monetary policy and the BOP, offering a framework for addressing economic challenges in a remittance-dependent, low-income economy like Nepal.